Relationship Between Middle School Students' Mathematical Understanding and Mathematical Attitude - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2015)
The purpose of this research is to develop an instrument for testing students' mathematical understanding (Study I), to search whether there is a correlation between middle school students' mathematical understanding and their attitudes towards mathematics and to present the correlation by analyzing it according to various variables (Study II). The reliability and validity studies which were conducted within the scope of Study I showed that the scale have practicable features. The Study II was carried out with 341 students who are studying in various grades of a middle school. 'Determining the Mathematical Understanding Levels Scale (DMULS)' and 'Mathematics Attitude Scale (MAS)' was used as data collection instruments. According to the results of the study; it was appeared that there was a positive and significant correlation at a high level between mathematical understandings of students and their attitudes towards mathematics and there was a positive and significant correlation at middle level between mathematical understandings of students and sub-dimension scores of mathematics attitudes scale. Besides, it was determined that the mathematical understanding of the students differed by gender but the attitudes of students towards mathematics did not differ by their genders and both mathematical understandings and attitudes of students differed significantly according to their grade levels.
Keywords: Mathematical Understanding; Attitude; Relationship; Validity; Relability; GROWTH